Exon and intron definition in pre‐mRNA splicing. (8th October 2012) - De Conti, Laura; Baralle, Marco; Buratti, Emanuele
Abstract One of the fundamental issues in RNA splicing research is represented by understanding how the spliceosome can successfully define exons and introns in a huge variety of pre‐mRNA molecules with nucleotide‐precision. Since its first description, researchers in this field have identified and characterized many fundamental elements and players capable of affecting the splicing process, both in a negative and positive manner. Indeed, it can be argued that today we know a great deal about the forces that make an exon, an exon and an intron, an intron. As will be discussed in this review, these decisions are a result of a complex combinatorial control resulting from many different factors/influences. Most importantly, these influences act across several levels of complexity starting from the relatively simple interaction between two consensus 5′ and 3′ splice sites to much more complex factors: such as the interplay between silencer or enhancer sequences, transcriptional processivity, genomic milieu, nucleosome positioning, and histone modifications at the chromatin level. Depending on local contexts, all these factors will act either antagonistically or synergistically to decide the exon/intron fate of any given RNA sequence. At present, however, what we still lack is a precise understanding of how all these processes add up to help the spliceosome reach a decision. Therefore, it is expected that future challenges in splicing research will be the careful characterization of all these influences to improve our ability to predict splicing choices in different organisms or in specific contexts. WIREs RNA 2013, 4:49–60. doi: 10.1002/wrna.1140 For further resources related to this article, please visit the WIREs website.